Technology Contribution Coefficient and Strategic Position of Knife Manufacturing IKM: Koefisien Kontribusi Teknologi dan Posisi Strategis Industri Manufaktur Pisau IKM - Maulana, Muhammad Naufal; Wahyuni, Hana Catur (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Technology capability plays a critical role in transforming raw materials into value-added products within small and medium manufacturing enterprises. Specific Background: Krian Custom Tools, a knife manufacturing IKM established in 2013, relies on technoware, humanware, infoware, and orgaware components to maintain product quality and production consistency. Knowledge Gap: The technological components had not previously been quantitatively measured to determine their contribution level and corresponding strategic direction. Aims: This study aims to calculate the Technology Contribution Coefficient (TCC) using the technometric method and formulate strategic recommendations through SWOT analysis. Results: The overall TCC value reached 0.805, categorized as very good and modern. Component sophistication values were 0.689, 0.880, 0.858, and 0.847, and all components were positioned in Quadrant I of the SWOT diagram. Novelty: The study integrates technometric evaluation and SWOT positioning within a knife manufacturing IKM context. Implications: The findings provide a structured basis for strategic technology development and decision-making in small-scale manufacturing enterprises. Keywords: Technology Contribution Coefficient, Technometric Method, SWOT Analysis, Technology Components, Small Medium Enterprise Key Findings Highlights Aggregate coefficient indicates advanced technological classification level All evaluated elements positioned in aggressive strategic quadrant Quantitative assessment supports structured development planning